A study of comparison of liquid-based cytology versus conventional pap smear for evaluation of cervical cytology at a tertiary healthcare hospital - Singh, Shruti; Gupta, Amit; Nath, D.; Shobha, Hema J. (International Journal of Research in Medical Sciences, 2019)
Background: Cervical cancer is the second highest cause of cancer-related mortality in women, and the only sign of this cancer in the early stages is the loss of abnormal cells. Clinical signs of the disease appear only after cancer has reached advanced stages. Conversely, this cancer in precancerous conditions is completely curable and screening with conventional Papanicolaou (CP) has reduced the mortality by 70% but it is also associated with a significant number of false-negative cases (20-50%). In 1996, liquid-based cytology (LBC) method was developed to overcome the disadvantages of the previous method expecting to have good features such as high sensitivity, faster sample preparation, and decreased the rate of inadequate smears. Methods: This descriptive-analytic study was conducted at the Department of Pathology and Department of Obstetrics and Gynaecology, government medical college, Datia for the period of 11 months from April 2018 to February 2019. The study includes total 80 subjects. Total No. of Pap smear examined (both LBC and CPS) are 160. Results: There were statistically significant differences of satisfactory/unsatisfactory rate, smear cellularity, background clarity and detection of endocervical cells, in between liquid based cytology and conventional Pap smear finding (p<0.05). Diagnostic efficacy i.e. sensitivity and specificity of LBC is greater than CPS for evaluation of cervical cytology. Conclusions: Results shows, that LBC may improve the sample’s quality, reduce the number of unsatisfactory smear and increases the diagnostic efficacy.